2022
DOI: 10.3390/jcm11123347
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Hormone Predicts Total Cholesterol and Low-Density Lipoprotein Cholesterol Reduction during the Acute Phase of COVID-19

Abstract: A complex dysregulation of lipid metabolism occurs in COVID-19, leading to reduced total cholesterol (TC), LDL-cholesterol (LDL-C), and HDL-cholesterol (HDL-C) levels, along with a derangement of thyroid function, leading to reduced thyroid-stimulating hormone (TSH) levels. This study aimed to explore the association between TSH levels during COVID-19 and the variation (Δ) of lipid profile parameters in the period preceding (from 1 month up to 1 year) hospital admission due to COVID-19. Clinical data of 324 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…On the other hand, they stated that TSH level decreases in COVID-19. So, they concluded that LDL level decreases in COVID-19 [ 46 ]. Zhao et al found that LDL levels decreased in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they stated that TSH level decreases in COVID-19. So, they concluded that LDL level decreases in COVID-19 [ 46 ]. Zhao et al found that LDL levels decreased in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[123][124][125] Another study has shown that older adults on statin therapy have a higher chance of developing asymptomatic COVID-19 as opposed to a symptomatic form of the disease. 126,127 Although extensive research pleads in favor of statin administration (in both pre-hospital and in-hospital settings) in COVID-19 patients, several uncharted findings are yet to be defined (a proven causal relationship between the use of statins and the beneficial effects, type of statins that provide better protection, role of drug interaction, impact of pre-existing comorbidities). 125,128 Many controversies surrounded the negative impact that ACE2 inhibitors or angiotensin receptor blockers (ARBs) might have on SARS-CoV-2 infections, primarily because these agents increase the expression of ACE2 receptors, promoting SARS-CoV-2 entry into the cell.…”
Section: Treatmentmentioning
confidence: 99%
“…Lp(a) was measured via nephelometry through an apo(a) isoformdependent assay (BN-II-System, Siemens HD). The Friedewald formula was used to calculate low-density lipoprotein (LDL) cholesterol [32]. The following clinical parameters were recorded among those obtained during physical examination at hospital admission: body mass index (BMI), respiratory rate, oxygen saturation (SpO 2 ), fraction of inspired oxygen (FiO 2 ), Glasgow Coma Scale (GCS), systolic blood pressure (SBP), and diastolic blood pressure (DBP) [33,34].…”
Section: Baseline Data Collectionmentioning
confidence: 99%